The effect of biological movement variability on the performance of the golf swing in high- and low-handicapped players - Bradshaw, E. J.; Keogh, J. W. L.; Hume, P. A.; Maulder, P. S.; Nortje, J.; Marnewick, M. (Research Quarterly for Exercise and Sport, 2009)
The purpose of this study was to examine the role of neuromotor noise on golf swing performance in high- and low-handicap players. Selected two-dimensional kinematic measures of 20 male golfers (n = 10 per high- or low-handicap group) performing 10 golf swings with a 5-iron club was obtained through video analysis. Neuromotor noise was calculated by deducting the standard error of the measurement from the coefficient of variation obtained from intra-individual analysis. Statistical methods included linear regression analysis and one-way analysis of variance using SPSS. Absolute invariance in the key technical positions (e.g., at the top of the backswing) of the golf swing appears to be a more favorable technique for skilled performance.